Scientific literacy in the context of initial chemistry teacher training: an integrative literature review - Meira de Araújo Cavalcante, Amanda (2025)
The aim was to analyze the productions developed on scientific literacy within the scope of pre-service chemistry teacher training. Bibliographic research, of the type of integrative literature review, was carried out in the annals of National Meeting on Research in Science Education (ENPEC) and National Meeting on Chemistry Teaching (ENEQ), in journals of the area of science teaching and chemistry teaching with Qualis A1 and A2, and in the Coordination for the Improvement of Higher Education Personnel (CAPES) catalog of theses and dissertations, from January 2017 to December 2023. The descriptor “scientific literacy” was used, and in a second search, the descriptor “pre-service teacher training”. Scientific literacy involves knowledge related to science and the didactic-pedagogical field, indicating that the types of research developed from this perspective are diverse and that reflections generated in the conceptions of undergraduate students contribute to the scientific literacy of pre-service chemistry teachers.